Vessel wall stiffness parameters and left ventricle remodeling in patients receiving renal replacement therapy - E. A. Praskurnichiy; I. E. Minyukhina (Российский кардиологический журнал)
Aim. To perform a comparative assessment of vessel wall stiffness parameters and left ventricle (LV) remodeling in groups of patients with arterial hypertension (AH) receiving renal replacement therapy (RRT) and patients with hypertensive heart disease.Material and methods. One hundred fifty eight people were examined: 32 patients on program hemodialysis (PG), 37 — after kidney transplantation (KT), 69 — with essential hypertension and 20 healthy volunteers. All patients underwent 24-hour blood pressure (BP) monitoring with an assessment of the parameters of daily vessel wall stiffness, aortic pressure and Mand B-mode echocardiography.Results. In groups of patients with PG and after KT, the central and peripheral blood pressure did not differ significantly. When comparing with the group of essential hypertension in RRT patients, with similar values of office systolic and diastolic BP, higher average values of peripheral and central BP were determined. An increase in the values of the pulse wave velocity in the aorta of more than 10 m/s was observed only in RRT patient groups. In all groups of patients with AH, BP and vessel wallConclusion. Patients receiving RRT have higher values of the average daily pulse wave velocity in the aorta, central BP and a longer period of an increase in the pulse wave velocity in the aorta during the day, higher vessel wall stiffness values, and less pronounced LV spherification than in patients with hypertensive heart disease and comparable values of office BP.